Utility of the joint index in newborn congenital heart disease screening - Mengwen Li; Dan He; Tingting Peng; Rui Liu; Binzhi Tang (Scientific Reports)
Abstract To examine the value of“joint index”in the early and rapid screening of congenital heart disease (CHD) in newborns. The study selected live-born neonates who were delivered in the Department of Obstetrics and Gynecology at Sichuan Provincial People’s Hospital from January 1, 2023 to December 31, 2023. Cardiac auscultation and pulse oximetry were performed at 6 h to 72 h after birth. To further elucidate the diagnosis and to analyze and compare the value of cardiac murmur, pulse oximetry, and the combination of cardiac murmur and pulse oximetry for the early diagnosis of CHD, cardiac ultrasonography was performed on newborns with positive screening for either cardiac murmur or pulse oximetry. The value of heart murmur, pulse oximetry, and their combination was assessed in the early diagnosis of CHD. A total of 3037 newborns were screened following the inclusion and exclusion criteria. Of them, a total of 304 positive cases were included in the present study and were divided into 3 groups: 142 cases in the heart murmur group, 99 cases in the oxygen saturation group, and 304 cases in the combined group of those who were positive for both heart murmur and/or oxygen saturation. A total of 215 cases of CHD were diagnosed via cardiac ultrasound in screen-positive newborns, including 26 cases of severe CHD. The top three types of CHD were atrial septal defect (33.95%), ventricular septal defect (26.05%), and arterial duct failure (20.47%). The diagnostic sensitivity, accuracy, and negative predictive value of the combined group were 100%, 97.07%, and 100%, respectively. These values were significantly higher than those of the heart murmur group and the oxygen saturation group (P < 0.01), and the overall difference among the three groups in terms of the positive predictive value was not statistically significant (P > 0.05). However, in the two-by-two comparisons within the groups, the positive predictive value of the combined group was greater than that of the oxygen saturation group, and the difference was statistically significant (70.72% vs. 50.89%; P < 0.05). The specificity of the combined group was 96.85%, which was lower than that of the murmur and oxygenation groups (98.37% vs. 98.55%; P < 0.01). However, considering the detection of severe CHD, a total of 14 cases of severe CHD were detected in patients with positive cardiac murmur and oxygenation in the combined group (53.83%), which was significantly higher than that in the murmur group (11.54%) and oxygenation group (34.62%, P < 0.01). The newborns can be screened for CHD using heart murmur auscultation combined with pulse oximetry, which is a convenient, sensitive, and accurate method. It can be utilized as an important tool for early clinical screening for CHD.